Age- and sex-related differences in risk factors for perioperative intra-aortic balloon pump application in patients undergoing coronary artery bypass grafting - Gao, Junyi; Zhao, Qing; Cheng, Yi (Frontiers in Surgery, 2024)
BackgroundAn intra-aortic balloon pump (IABP) is a mechanical circulatory device frequently used in patients undergoing coronary artery bypass grafting (CABG). As a treatment for perioperative haemodynamic instability, IABP insertion often implicates an adverse outcome. This study aimed to investigate the age- and sex-related disparity in risk factors for perioperative IABP insertion in CABG patients.MethodsA total of 2,460 CABG patients were included and divided into subgroups by age (elderly subgroup, ≥65 years; young subgroup, <65 years) and sex. Basic characteristics were compared between IABP and non-IABP patients in the overall patient group and the subgroups. Multivariate logistic analysis was used to investigate the significant risk factors for perioperative IABP application, and interaction effects among the potential risk factors were analysed. Combined receiver operating characteristic analysis was used to evaluate the prediction value of combined risk factors.ResultsThe overall patient group had a mean age of 61.5 years. The application rate of perioperative IABP was 8.0%. A left ventricular ejection fraction (LVEF) <50% significantly correlated with perioperative IABP application in the overall patient group and the subgroups. Traditional factors such as myocardial infarction history, atrial fibrillation history, and intraoperative estimated blood loss were significant risk factors in certain subgroups. Small dense low-density lipoprotein levels were significantly associated with IABP insertion in the male subgroup and young subgroup. The area under the curve of combined risk factors was significantly higher than that of LVEF <50% alone in the overall patient group and subgroups.ConclusionAge- and sex-related differences were present in the risk factor distribution for perioperative IABP insertion in CABG patients.